EXTENDED PRODUCER RESPONSIBILITY FOR PLASTIC WASTE: A STRATEGIC MANAGEMENT ACCOUNTING PERSPECTIVE IN INDONESIA - Aliya Dimarizkya; Dita Hikmawaty Oktavia Ningrum; Yanuar Ramadhan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
These studies aim for research Implementation of Extended Producer Responsibility (EPR) in the Consumer Goods Industry in Indonesia. Extended Producer Responsibility (EPR) is policies that require manufacturer for responsible answer to products produced in the phase post consumption including packaging. Application policy This expected can reduce embossed rubbish plastic and push practice sustainable business. Research​ This use Systematic Literature Review (SLR) method for various studies national and international related EPR implementation and role accountancy management strategic in context sustainability. Study results show that the implementation of EPR in Indonesia is still not optimal and new adopted by some companies that have commitment to sustainability in its business strategy. Findings this also confirms importance integration information cost environment in the planning and decision-making process decision managerial as part from accountancy management strategic. With Thus, accounting management strategic play a role important in support EPR implementation, improving efficiency source power, as well as strengthen responsible consumption and production​ answer in accordance with Sustainable Development Goals (SDG) 12.